KARAKTERISTIK JASA RUMAH SAKIT DALAM PERSPEKTIF MANAJEMEN RUMAH SAKIT: INTEGRASI KUALITAS LAYANAN DAN PENGALAMAN PASIEN - Delima Cheryka; Dewi Ayu Wardhani; Eka Wisarini Putri; Elang Muhammad Firdaus; Fatimah Fatimah; A Rohendi (CV. Denasya Smart Publisher, 2026)
Hospitals are healthcare service organizations with complex characteristics, as the services provided are directly related to patient safety, clinical quality, and quality of life. In recent years, hospital service characteristics have evolved in response to increasing demands for service quality, greater attention to patient experience, and the accelerated adoption of digital technologies in healthcare delivery. These developments require a more comprehensive understanding from a hospital management perspective. This article aims to analyze the characteristics of hospital services from a hospital management perspective, with particular emphasis on the integration of service quality, patient experience, patient-centered care, and service digitalization. This article employs a conceptual-analytic approach based on a literatur review. The analysis is conducted through the examination and synthesis of concepts and findings from previous studies related to hospital service characteristics and hospital management published between 2020 and 2025. The literature is used as a theoretical foundation and conceptual reference to build an analytical framework, rather than as the object of a systematic review. The analysis indicates that service quality remains a fundamental foundation of hospital services, particularly in ensuring patient safety and clinical quality. However, service quality alone is no longer sufficient to explain the overall value of hospital services. Patient experience has emerged as a strategic dimension influencing patient satisfaction, trust, and hospital reputation. Furthermore, the implementation of patient-centered care strengthens the shift in service orientation toward patient needs, while digitalization reshapes interactions between patients and healthcare providers. In conclusion, hospital service characteristics are multidimensional and need to be managed in an integrated manner. Hospital management is required to combine clinical quality, service processes, patient experience, and organizational readiness for digital transformation in order to deliver patient-oriented and sustainable healthcare services.